A Simple Method to Estimate Tobacco-related Lung Cancer Deaths Based on Smoking Prevalence Data - Winkler, V.; Gbangou, A.; Kouyate, B.; Becher, H. (Methods of Information in Medicine, 2006)
Objective: Tobacco is the major cause of cancer and a relevant risk factor for several other chronic diseases. Due to the epidemiological transition in developing countries with overall increasing life expectancy there is an increasing relevance of chronic diseases to the total burden of diseases. Furthermore, there are indications for a rise in the consumption of tobacco products in developing countries. Since in Africa data on smoking prevalence are scarce and cancer diagnosis is often imprecise or missing, it is difficult to estimate the current and future number of cancer cases attributable to tobacco smoking. In this paper, we present an approach to estimate the effects of smoking on lung cancer in selected developing countries in Africa.Methods: We combined data on smoking prevalence from different African countries with estimates on age-specific lung cancer rates in smokers and non-smokers from industrialized countries and data on age and sex distribution in African countries. We perform a sensitivity analysis to evaluate the effect of the assumptions necessary for the procedure.Results: If the smoking prevalence in African countries will remain on the current level, we estimate age-specific lung cancer rates lower than those in Germany. Despite the relatively small proportion of adults aged 50 and more which is the age when most cancer cases occur, there is an appreciable number of deaths from lung cancer that could be prevented when smoking prevalence could be reduced. Depending on assumptions we estimate up about 50,000 lung cancer deaths per year in Africa, most of which could be prevented.Conclusions: Efforts for smoking prevalence reduction are much more needed in the developing world. Better and more comprehensive data on smoking are needed for more precise estimates.
Keywords: Lung cancer; smoking; Africa